2021
DOI: 10.3390/cancers13153776
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Lung Immune Prognostic Index with Immunotherapy Outcomes in Mismatch Repair Deficient Tumors

Abstract: Background: MSI-H/dMMR is considered the first predictive marker of efficacy for immune checkpoint inhibitors (ICIs). However, around 39% of cases are refractory and additional biomarkers are needed. We explored the prognostic value of pretreatment LIPI in MSI-H/dMMR patients treated with ICIs, including identification of fast-progressors. Methods: A multicenter retrospective study of patients with metastatic MSI-H/dMMR tumors treated with ICIs between April 2014 and May 2019 was performed. LIPI was calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The LIPI is composed of dNLR and LDH. Compared with the dNLR and LDH alone, the LIPI could better represent the inflammatory status and predict the prognosis of cancer patients (31). At present, the predictive role of the LIPI in osteosarcoma patients has not been reported.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The LIPI is composed of dNLR and LDH. Compared with the dNLR and LDH alone, the LIPI could better represent the inflammatory status and predict the prognosis of cancer patients (31). At present, the predictive role of the LIPI in osteosarcoma patients has not been reported.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, an increasing number of studies have shown that hematological markers (such as the neutrophil-lymphocyte ratio (NLR), platelet-lymphocyte ratio (PLR), lymphocyte-monocyte ratio (LMR), and serum lactate dehydrogenase (LDH)) are associated with the prognosis of various cancers, including osteosarcoma (23)(24)(25)(26)(27)(28). More surprisingly, some hematological markers, such as the lung immune prognostic index (LIPI), can predict the response to immunotherapy by reflecting the proinflammatory status (29)(30)(31)(32)(33). Therefore, it is reasonable to speculate that these hematological markers could assist in judging the nature of IPNs.…”
Section: Introductionmentioning
confidence: 99%
“…LIPI was relevant with inflammatory status and has recently been widely reported as a novel prognostic factor in lung cancer and extra-pulmonary cancer ( Mezquita et al, 2018 ; Kazandjian et al, 2019 ; Sonehara et al, 2020 ; Auclin et al, 2021 ; Feng et al, 2021 ; Veccia et al, 2021 ; Xie et al, 2021 ; Obayashi et al, 2022 ). More inspiring, studies have shown that LIPI can not only predict the survival but also excellently predict the response to immunotherapy ( Mezquita et al, 2018 ; Auclin et al, 2021 ; Feng et al, 2021 ). However, to the best of our knowledge, the prognostic predictive effect of LIPI has never been investigated in osteosarcoma yet.…”
Section: Discussionmentioning
confidence: 99%
“…According to Mezquita et al (2018) the combination of baseline LDH and dNLR, also named Lung Immune Prognostic Index (LIPI), is a novel index for predicting the benefit from immune checkpoint inhibitor and predicting OS or progression-free-survival (PFS) in lung cancer ( Kazandjian et al, 2019 ; Sonehara et al, 2020 ). The role of LIPI was also explored in extra-pulmonary cancers ( Auclin et al, 2021 ; Feng et al, 2021 ; Obayashi et al, 2022 ). However, as far as we know, the prognostic predictive ability of LIPI remains unclear in osteosarcoma.…”
Section: Introductionmentioning
confidence: 99%
“…The lung immune prognostic index (LIPI), combining LDH and the dNLR, was first introduced by Mezquita et al in metastatic non-small-cell lung cancer (NSCLC), in which pretreatment LIPI was associated with poor outcome for immune checkpoint inhibitors (14). Other studies also demonstrated the prognostic ability of the LIPI in extrapulmonary cancer (15)(16)(17). Nonetheless, the prognostic effect of the LIPI has not been explored in osteosarcoma.…”
Section: Introductionmentioning
confidence: 99%